The role of mesenchymal cell-mediated paracrine signalling in breast cancer progression and metastasis - Pal, Amarnath (2019)
Breast cancer (BC) is the second most common cancer type and a major health issue responsible for death in women. Paracrine signalling actively participates in normal breast development and also play a crucial role in breast cancer cell (BCC) proliferation and invasion. Previous indirect 2D co-culture studies have demonstrated the possibility that mesenchymal stem cells (MSCs) promote BC progression through secretion of paracrine factors including growth factors, cytokines and chemokines. This effect may therefore also occur in the tumor microenvironment (TME) within patient tumors. However, very little is known regarding the influence of MSCs on BCCs in mixed cell populations (direct co-culture) in 2D cell culture. Therefore, investigating the paracrine effect of MSCs in switching ductal carcinoma in situ (DCIS) into invasive ductal carcinoma (IDC) using 2D co-culture may facilitate identification of targeted therapeutics to treat BC in patients. However, failure of 2D cell culture model in representing the natural TME limits the scope of the discovery of the potential targeted therapeutics to treat advanced BC in patients. Since 3D spheroid models are more representative of a number of aspects of tumour biology, the spheroid model is considered a promising pre-clinical tool for drug discovery. Therefore, in parallel with 2D co-culture, for the first time in this study a BCC spheroid co-culture model incorporating MSCs was used in order to investigate the impact of MSCs on the BC progression. The BCC proliferation capacity of MSCs in 2D and spheroid models was determined by several in vitro assays and further confirmed by increased Ki-67 expression in BCC in the spheroid co-culture model. Beyond determining the effect of MSCs on BCC proliferation, the epithelial-mesenchymal transition (EMT)-inducing property of MSCs in non-invasive BCC in the co-culture models was also investigated in this study. An alteration in the phenotype was observed including cytoskeletal rearrangement and changes in expression of E-cadherin (downregulated) and vimentin (upregulated) in BCCs in the 2D co-culture, together highlighting the induction of EMT in the BCCs in the presence of MSCs. Similarly, the EMT-promoting effect of MSCs in BCC was determined through histology in the spheroid co-culture, which was consistent with an increased migration in the non-invasive BCCs, including in DCIS patient-derived BC xenografts (PDXs) incorporating MSCs.